PERAN SEKTOR PARIWISATA DALAM PENINGKATAN PAJAK DI KABUPATEN TORAJA UTARA - Gusti Anom Wijaya (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
The purpose is to measure the realization of hotel and restaurant tax revenue, the effectiveness of the realization of hotel and restaurant tax revenue, the growth rate of hotel and restaurant taxes, and the effect of the number of tourist visits on hotel and restaurant tax receipts in North Toraja Regency. The analysis used in this study is the analysis of the target and realization of hotel and restaurant taxes, analysis of hotel and restaurant tax effectiveness, hotel and restaurant tax growth, hotel and restaurant tax forecasting and SWOT analysis. The Research was carried out during 2009 to 2019.  The research results prove that the realization of hotel and restaurant tax revenues has continued to decline. Although it has decreased, the results of the analysis of the effectiveness on average are categorized very effective. The growth of hotel and restaurant taxes also always experience positive growth, except in 2019. The number of tourist visits has a very significant effect on the realization of hotel and restaurant tax revenue.